2022
DOI: 10.1128/mbio.03168-21
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase RNF5 Facilitates SARS-CoV-2 Membrane Protein-Mediated Virion Release

Abstract: Enveloped virus particles are released from the membranes of host cells, and viral membrane proteins (M) are critical for this process. A better understanding of the molecular mechanisms of SARS-CoV-2 assembly and budding is critical for the development of antiviral therapies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
6
38
0
Order By: Relevance
“…In contrast, the host also utilizes the ubiquitin-proteasome system (UPS) to destabilize viral proteins such as deubiquitination by the deubiquitinating enzyme (DUB) USP21 of the HIV-1 protein Tat, which leads to Tat instability ( 10 ). Recent reports have shown that the E3 ubiquitin ligases RNF5 and CRL2 (ZYG11B) are recruited by membrane protein and ORF10 protein of SARS-CoV-2, respectively; However, CRL2 is dispensable for SARS-CoV-2 infection ( 11 , 12 ). Guo et al reported that DUB USP13 is hijacked by SARS-CoV-2 nsp13 and prevents its degradation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the host also utilizes the ubiquitin-proteasome system (UPS) to destabilize viral proteins such as deubiquitination by the deubiquitinating enzyme (DUB) USP21 of the HIV-1 protein Tat, which leads to Tat instability ( 10 ). Recent reports have shown that the E3 ubiquitin ligases RNF5 and CRL2 (ZYG11B) are recruited by membrane protein and ORF10 protein of SARS-CoV-2, respectively; However, CRL2 is dispensable for SARS-CoV-2 infection ( 11 , 12 ). Guo et al reported that DUB USP13 is hijacked by SARS-CoV-2 nsp13 and prevents its degradation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with data obtained with other viruses, the role of secretory autophagy in CoV egress has also been considered (Yuan et al, 2022). However, the detailed mechanisms of this process, which until now have been predominantly described in the case of cytosolic proteins, remain poorly understood.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, the biogenesis of the DMVs engages the machineries operating in autophagy (Blanchard & Roingeard, 2015;Twu et al, 2021), with possible additional contribution from peroxisomes (Cortese et al, 2020). The autophagic pathway has also been implicated as an egress route for SARS-CoV-2 virus particles in light of ubiquitination of the M protein (Yuan et al, 2022). Following replication and transcription of viral RNAs, the genomic and subgenomic mRNAs leave the DMVs, most likely through special pores (Wolff et al, 2020).…”
Section: Virus Rna Repli C Ati On and Protein Synthe S Ismentioning
confidence: 99%
“…As a result of this mechanism, the virion also includes a nucleocapsid, i.e., a complex of N protein with RNA. A similar functional advan tage of the Cterminus over the transmembrane seg ments of the protein molecule was observed in the assembly of SARSCoV2 virions [43]. The purpose of M protein binding to the nucleocapsid complex for this coronavirus is considered in [44]: the authors assume that this complex is a certain stabilizer of the Cterminus, which, in turn, ensures an increase in the number of formed virions.…”
Section: Functions Of M Protein In the Processes Of Virion Assemblymentioning
confidence: 79%